L’eau de Chartreuse, miroir réfléchissant du renouvellement des dialectiques territoriales entre villes et montagne - Bérangère Serroi; François Besancenot; Philippe Brégard; Gérard Hanus; Fabien Hobléa (Revue de Géographie Alpine)
The Chartreuse Regional Nature Park is often considered a raw water reservoir for its borderlands. Although it is an abundant resource, current and expected impacts of climate change are already reflected in the emerging pressures on different water uses. These new challenges imposed on water resources raise questions about the relationships between urban and mountain areas, typically considered through the centre/periphery paradigm. In particular, this article deals with the question of transfers between water basins. In so doing, it analyses the new management strategies that communities have adopted and explores possible synergies against a backdrop of the power relationship between private and public management in order to move towards an approach that embraces solidarity and security of supply.